A Buddhist Framework for Building Youth Capacities for Peace through Technical and Vocational Education and Training (TVET) - Ngoc Bich Ly Le (International Journal of Interreligious and Intercultural Studies, 2022)
In our world today, violence permeates every aspect of life from conflict to peaceful settings. Peacebuilding requires collective effort. Educating everyone to be capable peacebuilder is the fastest way to achieve this collective peace. Shaping all education systems toward peacebuilding is a way to do this. This paper deals with how to turn TVET into peace-oriented program. While existing studies that link TVET and peacebuilding focus on how the program itself contributes to addressing conflict drivers in the larger society, this paper contributes a framework for internal human cultivation of TVET learners to be capable peacebuilders in their world of work. Youth is the target group because they are the dominant participants of TVET programs around the world and they are seen as the future of their nation. Based on a grounded-theory approach and reinterpretation of the Buddha’s teachings in the Sutta Pitaka, this paper constructed a Buddhist framework for holistic vocational training that builds youth capacities for peace. This framework has four components: job skills, work attitudes, work ethics, and wisdom. The paper also gives recommendations on how to apply this framework to improve TVET in the future. The paper argues that for the common goal of peace, future peace-oriented TVET needs wisdom from local cultures and religions to enrich the knowledge and be rooted in the local context.